PURE APPROACHES TO GHAZAL POETS OF TODAY TAJIK SPEAKING POETS (Scientific journal of the Fergana State University, 2023)
Today's Persian-Tajik literature of Uzbekistan, in our opinion, is divided into five parts of poetry of the period of independence (self-awareness, social, mystical, romantic, pictorial). Of course, there will be a lot of debate on this issue, as every point of view requires a different point of view, everyone speaks from his own point of view and preference. Since the literature of the period of independence is evolving and developing year by year, therefore, the Persian literature of Uzbekistan needs to be reviewed and thoroughly reviewed. The period of independence of Uzbekistan plays a significant role in the formation of Persian-Tajik literature. In this period, Tajik Persian literature is very rich and colorful in terms of form, content and subject, and covers a wide range of visual and expressive arts.Poets such as Paymon, Abdullah Subhan, Jaafar Muhammad, Normurad Karimzoda, Fazil Shukurzod, Zebo Tahirian, Shohid, Ozarmehr, Khoja, Pariso, Saida Sinavi, Asadullah, Shahzoda, Dilshodi Farhodzod, Olim Panjizoda, Sadriddin Hushyari, Saleh Muhammad, Odil Komil, Faiz Mahmud, Khosravi Sadullah and others entered the field of literature of the independence period with their excellent poems. The mentioned poets entered the field of literature with high poetry and understanding of responsibility. The poets of this period can be divided into three groups according to the content and form of their poems: poets who are inclined to traditional poetry; poets who prefer modern poetry and poets who write both modern and traditional poetry.